A Comprehensive Review on Effects of Nanoparticles-antioxidant Additives-biodiesel Blends on Performance and Emissions of Diesel Engine - Reddy, S. Naresh Kumar; Wani, M. Marouf (Applied Science and Engineering Progress, 2020)
The present review investigates the effects of different nanoparticles and antioxidants blended with biodiesel on the diesel engine’s performance and emission characteristics. Biodiesel usage in diesel engine decreases the dependence on imported petroleum and yields benefits like reduction in global warming and engine exhaust emissions. However, inherent drawbacks like lower calorific value (CV), higher density, and viscosity while increased fuel consumption and nitrogen oxides (NOx) emissions limit the biodiesel application in engines. In this way, the additives in the form of nanoparticles of different materials and antioxidants play a prominent role in mitigating the drawbacks of biodiesel. This review paper focuses on the effect of various additives in the form of nanoparticles and antioxidants blended with biodiesel on engine performance and emission characteristics. Biodiesel blended with additives reveals that the reduction of carbon monoxide (CO), unburnt hydrocarbons, and NOx emissions and also improvement in brake thermal efficiency (BTHE) and brake specific fuel consumption (BSFC) as compared to diesel and neat biodiesel. The comprehensive review suggests that nanoparticles of different materials and antioxidants blending with biodiesel improved its characteristics and also establish an optimum improvement in engine performance and emission characteristics.